Alternative in-vivo models of mucormycosis - Scheler, Jakob; Binder, Ulrike (Frontiers in Cellular and Infection Microbiology, 2024)
Mucormycosis is still regarded a rare fungal infection, but the high incidences of COVID-associated cases in India and other countries have shown its potential threat to large patient cohorts. In addition, infections by these fast-growing fungi are often fatal and cause disfigurement, badly affecting patients’ lives. In advancing our understanding of pathogenicity factors involved in this disease, to enhance the diagnostic toolset and to evaluate novel treatment regimes, animal models are indispensable. As ethical and practical considerations typically favor the use of alternative model systems, this review provides an overview of alternative animal models employed for mucormycosis and discusses advantages and limitations of the respective model.